2014
DOI: 10.1016/s2305-0500(13)60182-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of follicular oxidant-antioxidant balance and oxidative damage during reproductive acyclicity in water buffalo (Bubalus bubalis

Abstract: 2016-12-23T18:47:23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…However, a negative correlation of THI with serum antioxidant enzymes was in agreement with earlier studies on dairy cows (57,58) and buffaloes (29). The decrease in activity of antioxidant enzymes during summer revealed a reduced total antioxidant capacity to manage the excessive load of ROS which has been associated with reproductive acyclicity in buffaloes, owing to severe damage to follicular cells (59). Usually non-lactating buffaloes are neglected in terms of management of heat stress as compared to lactating animals, which subsequently affects their reproductive performance.…”
Section: Association Of Thi With Physiological and Biochemical Paramesupporting
confidence: 90%
“…However, a negative correlation of THI with serum antioxidant enzymes was in agreement with earlier studies on dairy cows (57,58) and buffaloes (29). The decrease in activity of antioxidant enzymes during summer revealed a reduced total antioxidant capacity to manage the excessive load of ROS which has been associated with reproductive acyclicity in buffaloes, owing to severe damage to follicular cells (59). Usually non-lactating buffaloes are neglected in terms of management of heat stress as compared to lactating animals, which subsequently affects their reproductive performance.…”
Section: Association Of Thi With Physiological and Biochemical Paramesupporting
confidence: 90%
“…Levels of oxidative damage were also significantly decreased in ovarian follicles from cyclic compared with acyclic water buffalos ( Bubalus bubalis ) (Jan et al, ). ROS have important signal functions during follicular development, but are also responsible for initiation of apoptosis in primordial, primary and antral follicles, whereas antioxidants protect against oxidative‐damage‐induced follicular apoptosis (Gupta et al, ; Jan et al, ). In addition, oxidative damage to germline DNA could result in genetic changes being transmitted to offspring via common genetic inheritance (mutations) and/or epigenetic inheritance, with deleterious consequences for offspring fitness (Velando, Torres & Alonso‐Alvarez, ).…”
Section: Discussionmentioning
confidence: 99%
“…To test the hypothesis that reproducing individuals have increased levels of oxidative damage, we next made categorical comparisons of breeders versus animals drawn from the same populations or social groups which had not bred. Available data for this comparison came from 15 studies of 11 species of mammals, and from 3 studies of 3 species of birds (Cederberg, Basu & Eriksson, 2001;Upreti et al, 2002;Tomruk et al, 2010;Bergeron et al, 2011;van de Crommenacker et al, 2011;Garratt et al, 2011Garratt et al, , 2013Fletcher et al, 2012;Oldakowski et al, 2012;Stier et al, 2012;da Silva et al, 2013;Yang et al, 2013;Cram et al, 2015;Jan et al, 2014;Schmidt, Blount & Bennett, 2014;Xu et al, 2014;Costantini et al, 2014b), and additional unpublished data from a study of banded mongooses (Mungos mungo) (see online File S1, Table S2). In a meta-analysis including all tissues and markers, there was no consistent association between reproduction and oxidative damage (Fig.…”
Section: (2) Reproductive State and Oxidative Damagementioning
confidence: 99%
“…This in turn is involved in modulation of estrous cycle and uterine environment causing defective embryo development and reproductive failure in buffaloes [68] and also contributes to the elongation of the postpartum anestrus [69]. Jan et al [70] found that overall greater concentrations of biomarkers of oxidative stress coupled with the reduced concentrations of total antioxidant capacity (TAC) in follicular fluid of acyclic buffaloes are indicative of the involvement of oxidative stress in the suspension of the ovarian activity. Further evidence showed that the oxidative stress and the depletion of the antioxidant activity play a significant role in diminished ovarian function, as evidenced by the significant increment in circulatory malondialdehyde (MDA) and simultaneous decline of TAC in buffalo heifers [71].…”
Section: The Effect Of Exogenous Melatonin On the Antioxidant Enzyme mentioning
confidence: 99%